ANALISIS KESALAHAN SISWA SMP DALAM MENYELESAIKAN SOAL PERSEGI PANJANG BERDASARKAN TEORI NEWMAN - Zulaida, Putri; Agustin, Miranti; Panjaitan, Chesia Aprina; Simanullang, Asria Ronauli; Fauzi, KMA (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze junior high school students' errors in solving rectangle problems based on Newman’s Theory. This research used a qualitative descriptive approach with 18 seventh-grade students of SMP Negeri 14 Medan as the subjects. Data were collected through a written test consisting of five essay questions, which were then analyzed based on Newman’s stages of errors, including reading errors, comprehension errors, transformation errors, process skill errors, and encoding errors. The results showed that students made errors at all stages of problem solving. The most dominant error was comprehension error at 61.11%, indicating that students still had difficulties in understanding the meaning of the problem and identifying the known and asked information. Furthermore, process skill errors at 50.00% and transformation errors at 38.89% showed that students were still less careful in calculations and were not yet accurate in determining the appropriate problem-solving strategy. Meanwhile, encoding errors at 27.78% and reading errors at 5.56% were found in lower percentages. These findings indicate that students’ conceptual understanding and thinking processes are still not optimal, so learning strategies that emphasize conceptual understanding, systematic problem-solving processes, and continuous practice are needed.